Retrospective Analysis of the Congenital Malformations in the Tertiary Center in Şanlıurfa - Sibel Sak; Mert Ulaş Barut; Emin Taşdüzen; Nurullah Peker; Muhammed Erdal Sak (Van Tıp Dergisi, 2019)
INTRODUCTION: The aim of this study is to determine the incidence, type and distribution of congenital anomalies that were diagnosed prenatally in a tertiary center of Sanliurfa which is the city that has the highest birth rate of Turkey. METHODS: Between January 2017 and December 2017, 68 patients who were referred to the Harran University Department of Obstetrics and Gynecology for fetal anomaly or whose fetal anomaly was diagnosed in our clinic were included in this study. Age, gravida, parity, abortus, number of living children, gestational week at diagnosis, gender, type of birth and fetal anomaly were obtained from patient files and termination ethics committee records. RESULTS: he 1631 births in our hospital were studied retrospectively. Sixtyeight fetüs with majör congenital anomalies were detected. The incidence of fetüs with congenital malformations was 4.17%, the most common isolated congenital anomaly was anencephaly. The fetüses with congenital anomaly were detected the most frequently in 21-34 age group pregnants, although it was detected rarely in pregnants group less than 20 years old (respectively 52.9 % and 19.1%, p<0.05). DISCUSSION AND CONCLUSION: The incidence of congenital malformation in our clinic, in Şanlıurfa city that has the highest birth rate of Turkey was 4.17 %. The ekstensive use of advanced ultrasound (USG), the training of pregnants for the importance of routine antenatal care and the increase in the number of experienced obstetricians will lead to a significant reduction in this ratio.